2018
DOI: 10.1039/c8gc00039e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic cascade conversion of furfural to 1,4-pentanediol in a single reactor

Abstract: The selective transformation of furfural to 1,4-pentanediol has been achieved with up to 90% yield in a CO2/H2/H2O system over Ru catalytic species supported on a mesoporous carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 39 publications
2
47
0
1
Order By: Relevance
“…The kinetic profiles of catalyitic reaction of 2-MeTF over supported Ni-Sn(3.0)/AlOH alloy catalyst are shown in Figure 7. It can be observed that 2-MeTF conversion increased gradually as a function of reaction time and achieved after a reaction time of 12 h. At earlier time, the products were dominated by 2H2MeTHF with maximum 21% in yield (after 2 h) then decreased gradually as the reaction time prolonged to reach almost constant after reaction time was extended up to 16 h. Meanwhile the amount of 2-MeTHF and 1,4-PeD was almost equal indicating the hydrogenation and hydrolysis of double bond of furang ring occurred in parallel as indicated in the previous reports [10,14,[39][40][41][42]. As the reaction times were prolonged, yield 1,4-PeD also increased smoothly to reach maximum 64% in yield after 12 h and then gradually decreased after a reaction time of 14 h. On the other hand, yield of 2-MeTHF increased gradually after the reaction time was extended up to 16 h.…”
Section: Kineticssupporting
confidence: 60%
See 1 more Smart Citation
“…The kinetic profiles of catalyitic reaction of 2-MeTF over supported Ni-Sn(3.0)/AlOH alloy catalyst are shown in Figure 7. It can be observed that 2-MeTF conversion increased gradually as a function of reaction time and achieved after a reaction time of 12 h. At earlier time, the products were dominated by 2H2MeTHF with maximum 21% in yield (after 2 h) then decreased gradually as the reaction time prolonged to reach almost constant after reaction time was extended up to 16 h. Meanwhile the amount of 2-MeTHF and 1,4-PeD was almost equal indicating the hydrogenation and hydrolysis of double bond of furang ring occurred in parallel as indicated in the previous reports [10,14,[39][40][41][42]. As the reaction times were prolonged, yield 1,4-PeD also increased smoothly to reach maximum 64% in yield after 12 h and then gradually decreased after a reaction time of 14 h. On the other hand, yield of 2-MeTHF increased gradually after the reaction time was extended up to 16 h.…”
Section: Kineticssupporting
confidence: 60%
“…NH3-TPD measurements show the differences in the surface acidity (e.g., part of strong acid, >923 K) between AlOH or -Al2O3 and AC supports ( Figure 4 and Table 1). The strong acid site may able to interact with C=C bond of furan ring, protonated, and then hydrolysed in presence of ethanol/H2O [40][41][42][43]. Note to be important that over AlOH or -Al2O3 supported Ni-Sn(3.0) catalysts, no side polymerization product was observed within the reactions.…”
Section: Catalyst Screeningmentioning
confidence: 99%
“…Depending on the process conditions [11], the nature of the catalyst [12], and the type of the solvent [13], furfural hydrogenation proceeds through various pathways and with the formation of a significant number of products. A variety of heterogeneous catalysts mainly based on Pd [14,15], Pt [16], Ni [17], Cu [18], and Ru [19]. supported on carbon [20], titanium oxide [21], alumina [22], silica.…”
Section: Introductionmentioning
confidence: 99%
“…Illustrative representation of reaction pathways in furfural hydrogenation.Other downstream products of furfural hydrogenation, such as (tetrahydro)furan [32], tetrahydrofurfural [33], lactones [34][35][36][37], levulinates [38,39], cyclopentanone(l) [40][41][42][43][44][45][46][47][48][49][50][51]. or diols [52][53][54][55], could also be employed as fuel additives, solvents, and platform molecules. Numerous studies on furfural hydrogenation have been published due to the attractive and broad range of applications of the aforementioned furfural-based compounds.…”
mentioning
confidence: 99%